Penguatan Rekognisi Hak-Hak Sipil pada Siswa Sekolah Dasar: Studi Kasus di SDS Muhammadiyah 4 Cawang Jakarta Timur - Ahmad, Mubarak; Ruslan, Ahmad; Nawawi, Muhammad Azhar; Pratama, Cahya Adhitya; Rizaldy, Rizkindo Junior (Jurnal Paedagogy, 2022)
This study aims to describe the conditions and foster a character of recognition for students of SDS Muhammadiyah 4 Cawang East Jakarta. The research uses the PAR (Participant Action Research) method with validity tests using Pre-Test and Post-Test to foster recognition character for students. Research fosters the character of recognition of learners as subjects by using indicators of self-knowledge, healthy socializing, bullying and gender education then use pre-tests and post tests to determine character growth in learners through these data. The results showed an increase in students regarding the growth of recognition character for strengthening Gender Education and the Principle of non-Discrimination as a form of civil rights in the school environment.